INDUCTION OF DRUG RESISTANCE IN PLASMODIUM FALCIPARUM: AN INTERMITTENT DRUG EXPOSURE METHOD - M.Nateghpour; S.A.Ward; R.E. Howells (Tehran University of Medical Sciences, 1998)
The production of experimentally induced drug resistance in the laboratory provides valuable opportunities for investigators to study the nature and genetics of drug resistance mechanisms to a given agent, patterns of cross resistance and the mode of action of drugs. At the beginning the continuous drug exposure was chosen as a standard procedure to produce drug- resistant strains of P. falciparum,.but later on some other methods were also applied. An intermittent drug exposure method as a novel procedure has been introduced in this study. Intermittent exposure of chloroquine resistant Kl and chloroquine sensitive T9.96 strains of P. falciparum to halofantrine culminated in a relatively rapid reduction in sensitivity to the drug. The response of halofantrifle - resistnat K1HF and T9.96 strains and parent parasites to halofantrifle, inefloquine, quinine and chloroquine was determined. The results indicated that the effectiveness of halofantrine to K1HF and T9.96HF strains decreased 9 and 3 folds respectively, compared to the parent parasites. Cross -resistance occurred among halofantrine. mefloquine and quinine. Halofantrine resistance was associated with enhanced chloroquine sensitivity in the strain derived from chloroquine - resistant K1 strain, hut not in the strain derived from chloroquine - sensitive T9.96 parasites.